Chemical Memory in a Three‐Reaction Dynamic System - Riera, Micaela Belen (2025)
In systems chemistry, a key goal is to design molecular networks that exhibit emergent behaviors beyond those of their individual components. Dynamic combinatorial libraries (DCLs), which consist of molecular species interconverting through reversible reactions, provide a powerful platform to achieve this. This study introduces a DCL constructed using reversible exchange reactions involving thiols, dithioacetals, thioesters, and disulfides. The library is organized into two distinct yet interconnected layers: one activated under acidic conditions via thiol/dithioacetal exchange, and the other responsive to basic conditions through thiol/thioester/disulfideexchange, with temperature further modulating these processes. The layers operate independently but share thiol intermediates, enabling redistribution of molecular components in response to environmental changes. Transient variations in pH or temperature alter the system’s connectivity, driving shifts in its final steady-state composition. Notably, the system encodes information about the nature and timing of these disturbances, which persists even after the external stimuli are removed. This "chemical memory" is reflected in the equilibrium state reached after 24 hours, offering new insights into how dynamic systems can retain environmental information.